Placebo and Nocebo Effects in Sexual Medicine: An Experimental Approach. Issue 8 (16th November 2016) - Kruger, Tillmann H. C.; Grob, Carolin; de Boer, Claas; Peschel, Thomas; Hartmann, Uwe; Tenbergen, Gilian; Schedlowski, Manfred
Abstract : Few studies have investigated placebo and nocebo effects in a human sexuality context. Studying placebo and nocebo responses in this context may provide insight into their potential to modulate sexual drive and function. To examine such effects in sexual medicine, 48 healthy, male heterosexual participants were divided into four groups. Each group received instruction to expect stimulating effects, no effect, or an inhibitory effect on sexual functions. Only one group received the dopamine agonist cabergoline; all other groups received placebo or nocebo. Modulations in sexual experience were examined through an established experimental paradigm of sexual arousal and masturbation-induced orgasm during erotic film sequences with instruction to induce placebo or nocebo effects. Endocrine data, appetitive, consummatory, and refractory sexual behavior parameters were assessed using the Arizona Sexual Experience Scale (ASEX) and the Acute Sexual Experience Scale (ASES). Results showed increased levels of sexual function after administration of cabergoline with significant effects for several parameters. Placebo effects were induced only to a small degree. No negative effects on sexual parameters in the nocebo condition were noted. This paradigm could induce only small placebo and nocebo effects. This supports the view that healthy male sexual function seems relatively resistant to negative external influences.